Cabazitaxel exhibits more favorable molecular changes compared to other taxanes in androgen‐independent prostate cancer cells. Issue 9 (24th June 2020) - Cevik, Ozge; Acidereli, Hilal; Turut, Fatma Aysun; Yildirim, Sahin; Acilan, Ceyda
Abstract: Taxane‐based chemotherapy drugs (cabazitaxel, docetaxel, and paclitaxel) are microtubule inhibitors, which are effectively and frequently used to treat metastatic prostate cancer (PCa). Among these, cabazitaxel is offered as a new therapeutic option for patients with metastatic castration‐resistant PC as that are resistant to other taxanes. Here, we investigated the cellular and molecular changes in response to cabazitaxel in comparison with docetaxel and paclitaxel in androgen‐independent human PCas. The androgen‐independent human PCa cell lines, PC3 and DU145, were treated with 1 to 5nM cabazitaxel, docetaxel, or paclitaxel, and assessed for cell viability (MTT assay), colony forming ability and migration (scratch assay). The induction of apoptosis was determined through measurement of mitochondrial membrane potential (JC‐1 assay) and caspase‐3 activity assay. The protein expression changes (caspase‐3, caspase‐8, Bax, Bcl‐2, β‐tubulin, nuclear factor‐κB [NF‐κB/p50, NF‐κB/p65], vascular endothelial growth factor, WNT1‐inducible signaling pathway protein‐1 [WISP1], transforming growth factor β [TGF‐β]) in response to drug treatment were screened via western blotting. Under our experimental conditions, all taxanes significantly reduced WISP1 and TGF‐β expressions, suggesting an anti‐metastatic/antiangiogenic effect for these drugs. On the other hand, cabazitaxel induced more cell death and inhibited colony formation compared to docetaxel or paclitaxel. The highest fold change in caspase‐3 activity and Bax/Bcl‐2 ratio was also detected in response to cabazitaxel. Furthermore, the induction of β‐tubulin expression was lower in cabazitaxel‐treated cells relative to the other taxanes. In summary, cabazitaxel shows molecular changes in favor of killing PCa cells compared to other taxanes, at least for the parameters analyzed herein. The differences with other taxanes may be important while designing other studies or in clinical settings.